Multiple Congenital Anomalies after Assisted Reproductive Technology in Japan (between 2004 and 2009). (11th November 2012) - Ooki, Syuichi
Abstract : Multiple congenital anomalies (MCAs) are defined as two or more unrelated major structural malformations that cannot be explained by an underlying syndrome or sequence. The percentage and combination patterns of MCAs were analyzed using the European surveillance of congenital anomalies computer algorithms for nationwide data on congenital anomalies after assisted reproductive technology between 2004 and 2009 in Japan. There were a total of 177, 548 pregnancies and 124, 846 live births. About 7% (96/1, 324) were MCAs. Although most maternal/neonatal outcomes between the isolated cases group and the MCAs group were similar, higher early neonatal death rate was observed in the MCAs group than in the isolated cases group (9.8% versus 3.7%, resp.). Regarding the major organ system subcategory in ICD-10, the rate of MCAs was around 30% in "congenital malformations of eye, ear, face, and neck, " "congenital malformations of the respiratory system, " and "congenital malformations of genital organs." On the other hand, the rate of MCAs was less than 10% in "congenital malformations of the circulatory system." The combination patterns of diseases were widely varied. Of them, two or three diseases of the circulatory system, the digestive system, and the musculoskeletal system tended to co-occur in the same individuals.